Analysis of Misogynistic Utterances in Elliot Rodger’s Manifesto as the Perpetrator of the 2014 Isla Vista Mass Killing - Anugerah Barzanzi Rahman Ginano; Frans Asisi Datang (Asosiasi Dosen Muda Indonesia, 2026)
An This study details about gender-based hate speech analysis targeting the female gender inside a manifesto written by Elliot Rodger, a killer virgin who was responsible for a mass attack in Isla Vista, California, United States in 2014. This research is based on forensic lingusitics platform, and using a qualitative approach with a critical discourse analysis based on Norman Fairclough’s model, which uses ideological-based approach. This research uses the manifesto itself as the base data, with quotes with female hate speech being taken as samples. The manifesto itself contains several quotes from degrading allthe way to suggesting that women should be eradicated due to the shooter’s perception of them failing to provide romantic relationships whilst a more attrractive male get them instead. The results suggests that the hate speech found inside the manifesto is a representation of hatred that Rodger shown as a motive behind the mass attack. The analyzed quotes are also connected to the incel ideology, which is inherently patriarchal, or dominated by the male gender.